Study on Carbon Monoxide Detector using Conventional and Plasma-Treated Gas Sensor - Kam, Yew Zun; Nayan, Nafarizal (Evolution in Electrical and Electronic Engineering, 2021)
Air pollution is one of the major concerns around the world. This is because air pollution will decrease the air quality of the surrounding which will weaken the immune system if exposed to long term. This paper focuses on the effect of plasma treatment using atmospheric pressure plasma on the sensing layer of the MQ-7 gas sensor which is made of tin (IV) oxide (SnO2). Two similar experiments are conducted to ensure the experiments are credible. One of the MQ-7 gas sensors will undergo plasma treatment using atmospheric pressure plasma needle jet (APPNJ), which will be named as plasma-treated MQ-7 gas sensor, and it will be used to detect the concentration of carbon monoxide with a conversional MQ-7 gas sensor. By the end of this paper, the carbon monoxide concentration detected by conventional and plasma-treated MQ-7 gas sensors is compared. The data show that the conventional MQ-7 gas sensors detected more carbon monoxide in the presence of smoke compared to plasma-treated MQ-7 gas sensors. The sensitivity of the MQ-7 gas sensor decreases after undergoing plasma treatment.